Study on factors affecting use and non-use of temporary contraceptive device among MWRA of Tharu community of Hansposa VDC, Sunsari district. (2014)
ABSTRACT: This study was carried out with the objective to generate the information on the status of use of temporary contraceptive devices and factors affecting it so that they can be used for program planning and implementation for the attainment of temporary contraceptive devices targets. A sample of 147 married women of reproductive age (MWRA) of Hansposa VDC was face-to-face interviewed using semi-structured questionnaire. This was completely a non-experimental cross-sectional study and the sampling method was systematic random sampling. The data were analysed using univariate frequency table and chi-square for bivariate analysis. The study revealed that 40% of respondents belonged to 27-36 years of age and 20% belonged to 37-46 years. The average age was 30 years with S.D 7.231 and the most common age was 25 years. Similarly, 71.4% respondents belonged to high economic status. 58.5% were illiterate; and 60% of respondent were found to be currently living with her husband for at least a month. 56.5% respondents opined that it was not necessary to have a son; and 57% of the respondents had inadequate knowledge while 43% had adequate knowledge about temporary contraceptive devices. Similarly, 95% of the respondents opined that temporary contraceptive devices and temporary contraceptive service provider were easily available at health facilities. Bivariate analysis showed that there existed no significant association between age, educational status, economic status, son preference, availability of temporary contraceptive devices, availability of temporary contraceptive service provider, knowledge about temporary contraceptive devices and use and non-use of temporary contraceptive devices. The bivariate analysis revealed significant relationship only between women currently living or not living with her husband for at least a month and use of temporary contraceptive devices and decision making power of women and use and non-use of temporary contraceptive devices. Since, women currently living with her husband for at least a month and decision making power has significant relationship with use of temporary contraceptive devices, the study recommended that women living with her husband should be made the target group while planning the awareness program regarding temporary contraceptive devices use and program related to women empowerment should be carried out respectively. Also, the program related to temporary contraceptive devices use must be carried out regardless of the age, educational status, economic status, son preference, temporary contraceptive devices and service provider availability and knowledge.